2008
DOI: 10.1002/humu.20777
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for allelic heterogeneity in Hartnup disorder

Abstract: Hartnup disorder is an autosomal recessive impairment of amino acid transport in kidney and intestine. Mutations in SLC6A19 have been shown to cosegregate with the disease in the predicted recessive manner; however, in two previous studies (Seow et al., Nat Genet 2004;36:1003-1007; Kleta et al., Nat Genet 2004;36:999-1002), not all causative alleles were identified in all affected individuals, raising the possibility that other genes may contribute to Hartnup disorder. We have now investigated six newly acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…On the other hand, he exhibited delayed development, including mental retardation, with abnormal cranial magnetic resonance findings and attention-deficit hyperactivity disorder. The manifestations of Hartnup disorder can vary, ranging from asymptomatic status to pellagra-like skin rashes, cerebellar ataxia, psychotic behavior, and mental and physical retardation [2]. In 43 cases of Hartnup disorder reviewed by Wilcken et al, 28 were reported to manifest a rash.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, he exhibited delayed development, including mental retardation, with abnormal cranial magnetic resonance findings and attention-deficit hyperactivity disorder. The manifestations of Hartnup disorder can vary, ranging from asymptomatic status to pellagra-like skin rashes, cerebellar ataxia, psychotic behavior, and mental and physical retardation [2]. In 43 cases of Hartnup disorder reviewed by Wilcken et al, 28 were reported to manifest a rash.…”
Section: Discussionmentioning
confidence: 99%
“…It is caused by an inborn error of neutral amino acid transporter in the apical brush border membrane of the intestines and proximal tubules of the kidneys [2]. Usually, Hartnup disorder takes a benign course.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients show an intermittent, unsteady, wide-based gait. Prognosis is usually benign [23–25]. Maple syrup urine disease (MSUD) is an AR disorder that involves branched-chain amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, 17 mutations have been described; the most common mutation is c.517G / A, which is found in 43% of affected patients. 42 Patients with Hartnup disease present with intermittent and recurrent symptoms with a variable spectrum. The onset of disease in children is 3 to 9 years of age.…”
Section: Hereditary Photodermatoses Caused By Abnormal Biochemical Sumentioning
confidence: 99%